Wehrmachtjustiz an der Heimatfront. Die Militärgerichte des Ersatzheeres im Zweiten Weltkrieg - Theis, Kerstin (Studien zur Zeitgeschichte, 2016)
This study paints a comprehensive picture of military justice in the Ersatzheer, or replacement army of the Wehrmacht, which had various home-front tasks. The author analyzes the operation of Ersatzheer military courts during the Second World War. She offers a general portrait of court personnel, and describes their attempts as an extended arm of the Wehrmacht to militarize society.